Hybrid ionogel electrolytes for high temperature lithium batteries - Lee, Jin Hong; Lee, Albert S.; Lee, Jong-Chan; Hong, Soon Man; Hwang, Seung Sang; Koo, Chong Min (ROYAL SOC CHEMISTRY, 2015)
Hybrid ionogels fabricated using 1 M LiTFSI in N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide (BMPTFSI) crosslinked with ladder-like structured poly(methacryloxypropyl) silsesquioxane (LPMASQ) were investigated as high temperature ionogel electrolytes for lithium ion batteries. In addition to the exceedingly low crosslinker concentration (similar to 2 wt%) required to completely solidify the ionic liquids, which provided high ionic conductivities comparable to the liquid state ionic liquid, these hybrid ionogels exhibited superior thermal stabilities (>400 degrees C). Rigorous lithium ion battery cells fabricated using these hybrid ionogels revealed excellent cell performance at various C-rates at a variety of temperatures, comparable with those of neat liquid electrolytes. Moreover, these hybrid ionogels exhibited excellent cycling performance during 50 cycles at 90 degrees C, sustaining over 98% coulombic efficiency. Highly advantageous properties of these hybrid ionogels, such as high ionic conductivity in the gel state, thermal stability, excellent C-rate performance, cyclability and non-flammability, offer opportunities for applications as high temperature electrolytes.
Keywords: COMPOSITE POLYMER ELECTROLYTES; IONIC LIQUIDS; MECHANICALLY COMPLIANT; SOL-GEL; POLYSILSESQUIOXANE; CHALLENGES; POLYPHENYLSILSESQUIOXANE; NETWORKS